St. Paul and Epicurus - DeWitt, Norman Wentworth (Book collections on Project MUSE., 1954)
Everyone who is interesting in the meaning of the Bible will find this a revealing study, for it opens up a new window on the New Testament, a window that was walled up centuries ago by prejudice. Professor DeWitt throws new light on the writings of the A.